Picture and Picture Learning Model to Improve Students’ Achievement in Writing Recount Text - Sari, Maya Puspita; Putri, Novi Hardiana; Zahriana, Eka; Safwan, Muhammad (JETLEE : Journal of English Language Teaching, Linguistics, and Literature, 2022)
The purpose of this study is to determine the application of the picture and picture learning model to improve student learning outcomes in learning English with recount text material. The research method used is classroom action research with 2 cycles of action. The results of this study indicate that the average value of the pre-cycle is 59.60 with the number of students who complete as many as 9 people and the percentage of classical completeness of 36%. In Cycle I, the average score increased to 67.20 with 18 students completing and the percentage of classical completeness was 72%. Cycle II the average value of students is 71.60 with the number of students who complete as many as 22 people and the percentage of classical completeness is 88%. After going through 2 cycles students are able to determine the composition of the recount text. The application of the picture and picture model can improve learning outcomes and students' activeness in writing recount text material.